Risk assessment of potential impact of mining development (linear infrastructure) on peatland ecosystems in the Ring of Fire region, Northern Ontario - Dabros, Anna; Antwi, Effah Kwabena; Waldron, Celina; Darko, Akua Nyamekye; Higgins, Kellina L. (Frontiers in Environmental Science, 2025)
The Ring of Fire (RoF) region in northeastern Ontario, Canada, is an emerging mining frontier rich in critical minerals including nickel, chromite, and copper. The RoF lies within Treaty No. 9 territory and is home to several Indigenous First Nations, including Marten Falls, Webequie, and Neskantaga. While promising significant economic benefits, the future development poses various environmental risks, and concerns about Indigenous consultation and consent. The RoF is found in the Hudson Bay Lowlands (HBL), one of the world’s largest peatland complexes that cover 90% of the HBL landscape. These peatlands play crucial roles in carbon storage, water regulation, and biodiversity maintenance. The region’s remoteness—540 km from urban centers and lacking all-season road access—requires development of significant infrastructure such as roads, airstrips, and transmission lines. In this review, researchers used the Bowtie Risk Assessment Tool (BRAT) to analyze environmental risks, focusing on planned construction of three major all-season roads and resulting peatland disturbance. Two primary threats emerged: (1) peatland drainage causing habitat loss (including for threatened species like woodland caribou), wildfire risk, and increased carbon emissions; (2) linear infrastructure impact such as edge effects, invasive species, hydrological alterations, and permafrost degradation. Climate change may exacerbate these effects, increasing risk of drought and wildfire. Preventive and mitigation strategies involve habitat protection, clustering infrastructure, optimized road construction, construction and maintenance of culverts, invasive species control, and wildfire management. In conclusion, while mining development in the RoF region could boost the economy, it poses significant threats to one of the world’s largest peatlands, risking increased carbon release and biodiversity loss. Indigenous communities would face social and cultural impacts, underscoring the need for sustainable development that respects environmental preservation and Indigenous stewardship.